Produção orgânica de café no Sítio Santa Cecília, em Glória de Dourados-MS - KOMORI, O. M. (2008)
Organizado por: Alberto Feiden, Milton Parron Padovan, Adalgiza Inês Campolim, Aurélio Vinícius Borsato, Ivo de Sá Motta, João Batista Catto, Tércio Jacques Fehlauer.